Large-bite bisphosphite, 1,3-C6H4OPOC10H6(μ-S)C10H6O2: synthesis, copper(I), and gold(I) complexes - Balakrishna, Maravanji S.; Kumar, Pawan; Punji, Benudhar; Mague, Joel T. (Journal of Organometallic Chemistry, 2010)
Large-bite bisphosphite ligand 1,3-C6H4{OPOC10H6(μ-S)C10H6O}2 (3), is obtained by reacting chlorophosphonite {OC10H6(μ-S)C10H6O}PCl (2) with resorcinol in the presence of triethylamine. Treatment of 3 with CuCl in 1:1 molar ratio produces a 1D-coordination polymer [CuCl{(–OC10H6(μ-S)C10H6O–)P(–OC6H4O–)P(–OC10H6(μ-S)C10H6O–)}-κP,κP]∞ (4) in good yield. Similar reaction of 3 with two equivalents of AuCl(SMe2) affords a dinuclear complex, [Au2Cl2{(–OC10H6(μ-S)C10H6O–)P(–OC6H4O–)P(–OC10H6(μ-S)C10H6O–)}-κP,κP] (5). Single crystal X-ray structures of the ligand 3 and the complexes 4 and 5 are reported. The gold complex 5 shows dimeric structure supported by strong Au···Au aurophilic interactions.